2010
DOI: 10.1111/j.1600-051x.2010.01581.x
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue volume augmentation by the use of collagen‐based matrices: a volumetric analysis

Abstract: Thoma DS, Jung RE, Schneider D, Cochran DL, Ender A, Jones AA, Görlach C, Uebersax L, Graf‐Hausner U, Hämmerle CHF. Soft tissue volume augmentation by the use of collagen‐based matrices: a volumetric analysis. J Clin Peridontol 2010; 37: 659–666. doi: 10.1111/j.1600‐051X.2010.01581.x. Abstract Objectives: The aim was to test whether or not soft tissue augmentation with a newly developed collagen matrix (CM) leads to volume gain in chronic ridge defects similar to those obtained by an autogenous subepithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
138
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(150 citation statements)
references
References 38 publications
9
138
1
2
Order By: Relevance
“…Moreover, it has also been observed that the tissues underlying the soft tissue grafts undergo remodeling processes as well [18]. This appears to affect not only soft tissues (in case of a split-flap), but also hard tissues in case the transplants are placed on top of bone [17,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has also been observed that the tissues underlying the soft tissue grafts undergo remodeling processes as well [18]. This appears to affect not only soft tissues (in case of a split-flap), but also hard tissues in case the transplants are placed on top of bone [17,29].…”
Section: Discussionmentioning
confidence: 99%
“…In order to replace the harvesting of autogenous tissue, new volume-stable cross-linked collagen matrices (VCMX) were developed allowing for soft tissue volume augmentation [16]. In vitro and preclinical data showed favorable histological and volumetric results in terms of tissue integration and volume gain [17][18][19]. Although recent clinical data show similar volume gain when 4 augmenting implant sites with SCTG or VCMX [20], long term data monitoring volume changes at implant sites are still scarce .…”
Section: Introductionmentioning
confidence: 99%
“…Namely collagen matrices made of collagen type I and III have been the field of interest in recent years. These substitute materials were evaluated in preclinical and clinical studies for gain of keratinized tissue around teeth and implants, for recession coverage, for ridge preservation and even for soft tissue volume gain (Schmitt et al, 2015, Rotundo and Pini-Prato, 2012, Nevins et al, 2011, Lorenzo et al, 2012, Jung et al, 2013b, Thoma et al, 2010, Cardaropoli et al, 2012. The currently available evidence suggests that these collagen matrices can be safely used, integrate well into surrounding tissue, increase tissue thickness and increase the width of keratinized tissue to an extent close to the gold standard, the autogenous tissue (Sanz et al, 2009, Thoma et al, 2012, Jung et al, 2011.…”
mentioning
confidence: 99%
“…These measurements are based on impressions taken at various time-points, the digitization and later superimposition of these images. In vitro, preclinical and clinical studies were performed and demonstrated that this technique is adequate and accurate and may well serve to analyze volumetric changes of tissues over time (Windisch et al, 2007, Thoma et al, 2010, Schneider et al, 2011. This technique has recently been applied to evaluate volumetric changes at implant sites, with follow-ups up to one year (De Bruyckere et al, 2015, Schneider et al, 2011, Sanz Martin et al, 2015.…”
Section: Introductionmentioning
confidence: 99%